Una familia de modelos de localización óptima para actividades indeseables : propuesta y aplicación con sistemas de información geográfica - Antonio Moreno-Jimenez (Unité Mixte de Recherche 8504 Géographie-cités, 1998)
The growing social interest on environmental issues has fostered the attention paid by various disciplines to problems of locating noxious facilities. During some years, the location theory, mainly developed to answer questions such as the best place for economic or social facilities, has also been considering this subject and has formulated several models to solve well-structured problems. Grounded on this trend, this paper, first of all, summarizes some limitations of existing models, and next proposes a unified optimization model that enlarges the scope of the former ones. Additionally, and incorporating different transformations of the basic model, it is shown how it can be adapted to solve a wider set of problems. Finally, and as an example, a simple application is carried out using a raster geographical information system.